#TITLE_ALTERNATIVE# - PASMA HARYANI (NIM. 101 07 057); Pembimbing Tugas Akhir : Dr. Agus Yodi Gunawan, TASYA
The oil (gas) …eld development consists of two subprocesses, drilling and production where is treated as sequential in nature. Drilling is perfomed from platform in which one can drill only one well at a time, while production has a production level of uncertainty. In this …nal project we will construct a mathematical model for oil and gas …eld develompent process with two approaches, deterministic and stochastic. For the deterministic case, drilling time for each well is considered to be equal, analogous for the produstion time. For stochastic case, time for drilling and production process follows a particular distribution pattern. Using Renewal Theory, the completion of a well and failure to produce economical amount of oil or gas are analogous to the failure of a componenty. The stochastic model is simulated for two distribution, exponential and gamma distributions. From this model we …nd a number of active wells at any time that is used to estimate the production rate in a …eld.